Pilot analysis of global ecosystems: agroecosystems - Wood, Stanley; Sebastian, Kate; Scherr, Sara J.; World Resources Institute. (International Food Policy Research Institute, 2000)
This analysis determines the extent of agricultural land use and assesses the status of agroecosystems on a global basis. The report is the most comprehensive mapping of global agriculture to date. It also shows ways to better understand and monitor changes in the capacity of the systems to provide sustainable goods and services.